Phonemes, rimes, vocabulary, and grammatical skills as foundations of early reading development: evidence from a longitudinal study. - Muter, V; Hulme, C; Snowling, M; Stevenson, J (2004)
The authors present the results of a 2-year longitudinal study of 90 British children beginning at school entry when they were 4 years 9 months old (range = 4 years 2 months to 5 years 2 months). The relationships among early phonological skills, letter knowledge, grammatical skills, and vocabulary knowledge were investigated as predictors of word recognition and reading comprehension. Word recognition skills were consistently predicted by earlier measures of letter knowledge and phoneme sensitivity (but not by vocabulary knowledge, rhyme skills, or grammatical skills). In contrast, reading comprehension was predicted by prior word recognition skills, vocabulary knowledge, and grammatical skills. The results are related to current theories about the role of phonological, grammatical, and vocabulary skills in the development of early reading skills.